Progress and outlook of experimental techniques in lacustrine shale reservoir characterization - Zhang, Yangyu; Li, Tengjia (Frontiers in Earth Science, 2025)
Shale reservoirs, as a significant category of unconventional oil and gas resources, possess substantial potential. Compared to marine shale reservoirs, lacustrine shale reservoirs are characterized by pronounced heterogeneity, complex pore structures, and limited seepage capability. Precise characterization of these reservoirs and elucidation of the mechanisms of oil and gas enrichment within micron- to nano-scale pore systems are critical challenges. Recent advancements in experimental techniques, such as microscopic computed tomography (CT), scanning electron microscopy (SEM), focused ion beam scanning electron microscopy (FIB-SEM), and energy-dispersive X-ray spectroscopy (EDS), along with the rapid development of large-view imaging and micron- to nano-scale structure modeling, have considerably enhanced the characterization of lacustrine shale reservoirs. These technological improvements facilitate high-precision identification of mineral compositions and structures, detailed modeling of micron- to nano-scale pores and fractures, and improved characterization and prediction of natural fractures and fluid occurrence characteristics. This paper aims to provide a systematic review of the experimental technological advances in characterizing lacustrine shale reservoirs, identify the primary challenges, and propose a perspective on future development trends. It seeks to offer a reference for refining high-precision characterization and evaluation techniques for lacustrine shale reservoirs, thus supporting more effective and sustainable resource exploitation.